Gramsci in the Folds of Posthegemony: Some Critical Notes on the Roots and Contradictions of a Theory - Tarascio, Giacomo (Res Publica. Revista de Historia de las Ideas Políticas, 2022)
The following essay introduces a survey on the theory of posthegemony and that part within it, which can be grouped under the definition of the foundational. This area of study is defined by the rejection of the relationship between subalternity and hegemony, declaring the end of the latter. The particularity of posthegemony lies in the root of this idea, derived from the intersection of the idea of subalternity within the Subaltern Studies and the theory of hegemony developed by Ernesto Laclau and Chantal Mouffe. From the perspective of the Gramscian studies, the two key conceptions of subalternity and hegemony will be analysed, in particular how they were elaborated in the two mentioned current at the basis of posthegemony. Subsequently, posthegemony itself will be analysed in its two main ramifications, one linked to infrapolitics and the other to the multitude.